ANALISIS YURIDIS MENGENAI PERANAN KEPOLISIAN DALAM PENANGAN TINDAK PIDANA CYBERCRIME DI MEDIA SOSIAL (Qawanin Jurnal Ilmu Hukum, 2021)
The objectives of this study are 1). to find out how the roles of the police in the investigation process in handling cybercrime crimes on social media, 2). To find out the factors that influence and what are the constraints that affect the handling of cybercrime crime on social media. This study uses a qualitative method that is presented descriptively. The location of this research is Polrestabe Makassar, while in this study using primary and secondary data sources. Data collection techniques through interviews and documentation. The results showed that the handling of cybercrime crime at the investigation stage is the same as the handling of criminal acts in conventional crimes, but it is distinguished by the slightly complicated arrest process because it has to coordinate with several parties, as for the factors that influence the handling of cyber crime, namely if There is intervention, and other factors, namely if the case becomes public attention, it is stated that sometimes the case cannot be continued but because it has become the public's attention, sometimes the case is forced or does not work as it should. The obstacles faced also vary from a lack of experts, often the perpetrators use anonymous accounts whose information cannot be known, to sometimes devices that are simply removed because search and seizure permits have not been issued.